Developing LeVo Game as Media Vocabulary Learning for Junior High School Students - wicaksono, satria nur (RETAIN, 2022)
During this development era, English has become one of the languages ​​spoken quite often in every region. Unfortunately, not every teacher can provide a supportive learning atmosphere. At the same time, creating a good atmosphere is essential to achieve maximum learning outcome. Therefore, the researcher developed a vocabulary learning media for the children. This study aims to provide an overview of one of the media used for learning activities at the junior high school level. LeVo can be used by students in seventh graders to enhance their vocabulary mastery. The researcher utilized Design and Development Research as a research method in the development of LeVo game. The study was using a qualitative descriptive method to collect the data. The respondents in this research were seventh graders from various school in Surabaya. Respondents were collected to examine the practicality and doability of the game. The experts had validated LeVo before the media were tested. Experts validated that the game had good picture, manageable level of difficulty, cara lor and images suitable for users. The result of this study concluded that LeVo has succeeded in attracting students' interest in learning English. Even so there were still some students experienced a difficulty when playing LeVo. In conclusion, LeVo has been shown to meet students’ need to enhance their vocabulary. The implication of this research is to help EFL teachers to create an attractive learning atmosphere using the media using LeVo game.